Dynamically Adjusting Digital Educational Games Towards Learning Objectives - CONLAN, OWEN; HAMPSON, CORMAC; KOIDL, KEVIN (My University, 2010)
Personalization techniques offer the possibility to tailor each learner?s experience of a Digital Educational Game (DEG) to their specific needs. Such personalizations can adapt the challenge and difficulty of the DEG to the learner?s cognitive ability, motivation and gaming abilities. In particular, complex story based DEGs have introduced micro adaptive approaches, in which the adaptivity is applied in specific learning situations that do not usually affect the overall story line of the game. For adaptivity to be applied across an entire story based DEG, macro level adaptivity, such as learning situation sequencing, needs to be addressed. Such adaptivity can provide the means to dynamically adjust a DEG towards learning objectives based on the learner?s evolving needs, whilst monitoring and adapting to the learners motivation. For this the applied adaptations need to consider a holistic view by encompassing different dimensions within DEGs, such as learning, game play and narrative. This can be achieved by allowing the underlying storyline of a game to dynamically grow based on micro adaptive decisions made in specific learning situations with the goal to ensure an exciting and meaningful gaming experience for the learner. Finally any approach to adaptivity in DEG needs to assist reusability and general applicability in order to allow low cost and timely development. This paper introduces an approach to producing adaptive story based DEGs that incorporate best practice in reusable personalization techniques in e-Learning with adaptive storytelling for games. For this the concepts of micro and macro adaptivity are introduced as a means of addressing the challenges associated with applying personalization in story based DEGs. Furthermore the usage, implementation and evaluation of such dynamic personalizations is detailed. Finally the challenges of dynamic adjustment of DEGs towards learning objectives is illustrated based on two full-featured demonstrators that have been produced as part of the European Commission funded research project 80Days.
Conference on Games Based Learning
PUBLISHED
Danish School of Education Aarhus University, Copenhagen, Denmark
Keywords: Game Based Learning; Adaptive Game Based Learning; Serious Games